Community Empowerment through Religious Education and Islamic Social-Resilience - Sitti Faoziyah (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
This research aims to examine the factors that contribute to the success of empowering Muslim communities in West Java Province's poorest neighborhoods through religious education, halal food security, and socio-religious resilience. Quantitative research techniques, specifically survey research, are employed here. A questionnaire was used to collect information from 185 people who were selected at random using a proportional sampling formula. Smart-PLS 3.0 was used to perform the statistical analysis. The study's findings suggest that the effectiveness of government and private-sector efforts to empower Muslim communities is impacted by the level of religious education given to the Muslim community, both in terms of broad-brush religious education and more specialized forms of education. A well-planned halal food security program has a higher chance of successfully empowering Muslims. A Muslim community's ability to empower itself is heavily influenced by the degree to which its members feel socially and religiously safe. Muslim community empowerment programs are carried out by the government, private institutions (NGOs and companies), and campuses; they are significantly influenced by religious education and life skills education, halal food security, and social-religion security.